Gold film-catalysed benzannulation by Microwave-Assisted, Continuous Flow Organic Synthesis (MACOS) - Shore, Gjergji; Tsimerman, Michael; Organ, Michael G. (Beilstein Journal of Organic Chemistry, 2009)
Methodology has been developed for laying down a thin gold-on-silver film on the inner surface of glass capillaries for the purpose of catalysing benzannulation reactions. The cycloaddition precursors are flowed through these capillaries while the metal film is being heated to high temperatures using microwave irradiation. The transformation can be optimized rapidly, tolerates a wide number of functional groups, is highly regioselective, and proceeds in good to excellent conversion.
Keywords: benzannulation; flow synthesis; gold catalysis; microwave; thin metal film

Microwave Assisted Organic Synthesis - Tierney, P. J.; Lidstrom, P. (Blackwell Publishing, 2005)

(untitled) - Kappe, C. O. (Angew. Chem., Int. Ed., 2004)

(untitled) - Jähnisch, K.; Hessel, V.; Löwe, H.; Baerns, M. (Angew. Chem., Int. Ed., 2004)

(untitled) - Pennemann, H.; Watts, P.; Haswell, S. J.; Hessel, V.; Löwe, H. (Org. Process Res. Dev., 2004)

(untitled) - Bremner, S.; Organ, M. G. (J. Comb. Chem., 2007)

(untitled) - Comer, E.; Organ, M. G. (J. Am. Chem. Soc., 2005)

(untitled) - Comer, E.; Organ, M. G. (Chem.–Eur. J., 2005)

(untitled) - Bagley, M. C.; Jenkins, R. L.; Lubinu, M. C.; Mason, C.; Wood, R. (J. Org. Chem., 2005)

(untitled) - Saaby, S.; Baxendale, I. R.; Ley, S. V. (Org. Biomol. Chem., 2005)

(untitled) - He, P.; Haswell, S. J.; Fletcher, P. D. I. (Appl. Catal., A, 2004)

(untitled) - Cablewski, T.; Faux, A. F.; Strauss, C. R. (J. Org. Chem., 1994)

(untitled) - Glasnov, T. N.; Kappe, C. O. (Macromol. Rapid Commun., 2007)

(untitled) - Glasnov, T. N.; Vugts, D. J.; Koningstein, M. M.; Desai, B.; Fabian, W. M. F.; Orru, R. V. A.; Kappe, C. O. (QSAR Comb. Sci., 2006)

(untitled) - Wilson, N. S.; Sarko, C. R.; Roth, G. (Org. Process Res. Dev., 2004)

(untitled) - Wiles, C.; Watts, P. (Eur. J. Org. Chem., 2008)

(untitled) - Wheeler, R. C.; Benali, O.; Deal, M.; Farrant, E.; MacDonald, S. J. F.; Warrington, B. H. (Org. Process Res. Dev., 2007)

(untitled) - Baxendale, I. R.; Hayward, J. J.; Ley, S. V. (Comb. Chem. High Throughput Screening, 2007)

(untitled) - Brivio, M.; Verboom, W.; Reinhoudt, D. N. (Lab Chip, 2006)

(untitled) - Wild, G. P.; Wiles, C.; Watts, P. (Lett. Org. Chem., 2006)

(untitled) - Watts, P.; Haswell, S. J. (Drug Discovery Today, 2003)

(untitled) - Jones, R. V.; Csajagi, C.; Szekelyhidi, Z.; Kovacs, I.; Borcsek, B.; Urge, L.; Darvas, F. (Chim. Oggi, 2008)

(untitled) - Kikutani, Y.; Kitamori, T. (Macromol. Rapid Commun., 2004)

(untitled) - Stonestreet, P.; Harvey, A. P. (Chem. Eng. Res. Des., 2002)

(untitled) - Vasudevan, D.; Basha, C. A. (Bull. Electrochem., 2000)

(untitled) - Shore, G.; Organ, M. G. (Chem.–Eur. J., 2008)

(untitled) - Shore, G.; Organ, M. G. (Chem. Commun., 2008)

(untitled) - Shore, G.; Morin, S.; Mallik, D.; Organ, M. G. (Chem.–Eur. J., 2008)

(untitled) - Shore, G.; Morin, S.; Organ, M. G. (Angew. Chem., Int. Ed., 2006)

(untitled) - Hashmi, A. S. K. (Gold Bull., 2003)

(untitled) - Asao, N. (Synlett, 2006)

(untitled) - Asao, N.; Nogami, T.; Lee, S.; Yamamoto, Y. (J. Am. Chem. Soc., 2003)

(untitled) - Hashmi, A. S. K.; Frost, T. M.; Bats, J. W. (J. Am. Chem. Soc., 2000)

(untitled) - Hashmi, A. S. K.; Frost, T. M.; Bats, J. W. (Org. Lett., 2001)

(untitled) - Asao, N.; Takahashi, K.; Lee, S.; Kasahara, T.; Yamamoto, Y. (J. Am. Chem. Soc., 2002)

(untitled) - Straub, B. F. (Chem. Commun., 2004)

(untitled) - Obika, S.; Kono, H.; Yasui, R.; Yanada, Y.; Takemoto, Y. (J. Org. Chem., 2007)

(untitled) - Dai, G.; Larock, R. C. (Org. Lett., 2001)

(untitled) - Dyker, G.; Stirner, W.; Henkel, G. (Eur. J. Org. Chem., 2000)

(untitled) - Barluenga, J.; Vasquez-Villa, H.; Ballesteros, A.; Gonzalez, J. M. (Org. Lett., 2003)

(untitled) - Asao, N.; Aikawa, A.; Yamammoto, Y. (J. Am. Chem. Soc., 2004)